Characterization of the bacterial communities of aerobic granules in a 2-fluorophenol degrading process - Duque, Anouk F. (2016)
Aerobic granular sludge constitutes a novel technology for wastewater treatment. This study focused on the effect of 2-fluorophenol (2-FP) shock loadings on the microbial community diversity present in aerobic granules before and after inoculation with a bacterial strain able to degrade 2-FP, Rhodococcus sp. strain FP1. After bioaugmentation, apart from strain FP1, five culturable bacteria were isolated from the 2-FP degrading granules, belonging to the following genera: Serratia, Chryseobacterium, Xanthomonas, Pimelobacter and Rhodococcus. The latter two isolates are able to degrade 2-FP. Changes in the aerobic granules’ bacterial communities related to 2-FP shock loadings were examined using denaturing gradient gel electrophoresis (DGGE) of 16S rRNA gene pool. Numerical analysis of the DGGE profiles showed high diversity with an even distribution of species. Based on cluster analysis of the DGGE profiles, the bacterial communities present in the aerobic granules changes were related to the sampling time and the 2-FP concentration fed.